2021
DOI: 10.20473/bikk.v33.3.2021.162-167
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Contact Dermatitis Due to Hand Hygiene in The Era of COVID-19

Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus is known to cause COVID-19 (Coronavirus Disease 2019), and it is rapidly spreading throughout the world that it is declared as a global pandemic. Hand hygiene is widely promoted as it is recommended to reduce the risk of COVID-19 transmission. Contact dermatitis is one of the risks of hand hygiene campaign during the COVID-19. Purpose: This study aimed to assess the parents' level of knowledge before and after health education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Research conducted by Damayanti stated that 82.61% of patient with contact dermatitis during the COVID-19 pandemic used antiseptic soap, while the rest used non-antiseptic soap. 15 Incorrect use of soap, such as not using moisturizer after handwash, can also cause contact dermatitis in patients. A 2017 study in North America stated that the most common cleanser that causes ACD and ICD is skin soap, such as liquid, lotion, and bars.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted by Damayanti stated that 82.61% of patient with contact dermatitis during the COVID-19 pandemic used antiseptic soap, while the rest used non-antiseptic soap. 15 Incorrect use of soap, such as not using moisturizer after handwash, can also cause contact dermatitis in patients. A 2017 study in North America stated that the most common cleanser that causes ACD and ICD is skin soap, such as liquid, lotion, and bars.…”
Section: Discussionmentioning
confidence: 99%
“…Occlusive, humectant, and emollient are the types of moisturizers to prevent OCD. The moisturizers must be immediately applied after washing hands and before wearing gloves (Damayanti et al, 2021;Rundle et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers in the COVID-19 isolation ward were required to follow the infection prevention procedures such as hand hygiene, use of surgical mask or N95 mask, goggles, face shield, coverall gown, safety shoes, and shoe covers. Hand hygiene can be performed in one of two ways: by washing hands with soap and water or by using a hand sanitizer with at least 60% alcohol (Damayanti et al, 2021;Lan et al, 2020). A survey in China reported that 97.0% (526 of 542) of first-line healthcare workers had skin damage as a result of the infection prevention procedures, with the nasal bridge being the most affected site (83.1%), followed by cheeks (78.7%), hands (74.5%), and forehead (57.2%) (Damayanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies emphasize the importance of education for the management of skin diseases. 2,5,6 Xerosis cutis is currently still the most common complaint related to a skin condition in the elderly population. However, many of them are still uninformed of this complaint.…”
Section: Introductionmentioning
confidence: 99%